The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17966/jmi.2020.25.3.57
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoepidemiological Trends and Features of Epidermophyton floccosum Infections in Korea: Between Year 1998~2007 and 2008~2019

Abstract: Background: The knowledge of the clinical features and changing epidemiology of dermatophytes helps in better managing them. Objective: This study investigated the recent epidemiologic characters of Epidermophyton floccosum from January 2008 to December 2019 and attempted to compare these with previous studies. Methods: The current study included 57 patients who visited our clinic and were diagnosed with E. floccosum infection through fungal culture between January 2008 and December 2019. Data on the date of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…Regarding patient demographics, prior studies have typically reported a higher male‐to‐female ratio in patients with dermatophytic infections 21,22 . Earlier research focusing on E. floccosum dermatophytosis also revealed a male predominance 8,19 . However, our study demonstrated an equal distribution of male and female patients (50% each) with E. floccosum dermatophytosis.…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…Regarding patient demographics, prior studies have typically reported a higher male‐to‐female ratio in patients with dermatophytic infections 21,22 . Earlier research focusing on E. floccosum dermatophytosis also revealed a male predominance 8,19 . However, our study demonstrated an equal distribution of male and female patients (50% each) with E. floccosum dermatophytosis.…”
Section: Discussioncontrasting
confidence: 46%
“…In Korea, the prevalence of this pathogen ranged from 3.9% in 1976-1980 to 0.01% in 2018-2019. 18,19 Cruz and Carvajal documented a similar trend in Chile, with E. floccosum isolation decreasing from 1.1% in 1990 to 0.2% in 2010. 8 In Italy, the frequency of E. floccosum dermatophytosis drastically decreased from 38.8% in 1980-1984 to 4.5% in 2005-2010.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations